Complexity Model for Predicting Oil Displacement by Imbibition after Fracturing in Tight-Oil Reservoirs - Aijun Chen; Yiqing Zhou; Rulin Song; Yangrong Song; Hanlie Cheng; David Cadasse (Complexity)
With the increasing difficulty of conventional oil and gas exploration and development, oil and gas resources have developed from conventional to unconventional, and the exploration and development of tight-oil reservoirs are highly valued. In view of the complexity of the influencing factors of oil-water spontaneous seepage after fracturing and the instability of reservoir recovery, this paper takes the tight sandstone reservoir of Yanchang Formation in the southern Ordos Basin as the research object. Based on the micro-nano pore throat characteristics of tight sandstone, the seepage experiment is carried out, and the theoretical model of seepage suction is constructed. The mechanism and influencing factors of suction and oil displacement after fracturing in tight reservoirs are analyzed. Based on the analysis of fluid buoyancy and gravity, a mathematical model of the oil-water spontaneous flow after fracturing was established, and its influencing factors were analyzed. The experimental results show that the pore throats of tight sandstone are mainly in micron- and submicron scale, and the reservoir permeability is related to the pore throat structure, oil-water interfacial tension, and wettability. After fracturing, with the increase of the fracture length, the seepage velocity gradually decreases. With the increase of fracture opening, the influence of buoyancy and gravity on seepage velocity increases. With the increase of the fracture number, seepage velocity also increases. The fracture helps to reduce the adsorption of oil droplets on the core surface and improve the efficiency of spontaneous imbibition and oil displacement of the core. The research results provide theoretical data support for enhancing oil recovery and have important application guiding significance for the operational reliability of manufacturing systems with complex topology and the complexity and operability of production operations in manufacturing systems.